Statistics and health care fraud: how to save billions - Ekin, Tahir (ASA-CRC Series on Statistical Reasoning in Science and Society, 2019)
Health care systems and fraud -- Describing health care claims data -- Sampling and overpayment estimation -- Predicting health care fraud -- Discovery of new fraud patterns -- Challenges, opportunities and future directions